02 - MOBILIZATION OF THE NERVOUS SYSTEM IN ORDER TO IMPROVE THE AMPLITUDE OF MOVIMENTS AND FLEXIBILITY OF THE ASSINTOMATIC INDIVIDUALS (Fiep Bulletin - online, 2011)
Mobilization of the Nervous System is a technique that focuses to restore the movement and the flexibility of the nervous system, promoting return to the normal functions, also observing positive replies in the muscular function, besides being able to be used for prevention of lesions in athletes. The objective of research was to analyze the effects of Neural Mobilization, as an European technique, on what concerns to the earning of movement amplitude (EMA) and flexibility on asymptomatic individuals. The sample was made of 13 male participants, with the age about 21 years (standardization deviation 3,4). They went through initial assessments and in each session. The protocol was determined using a bilateral series for nerves: median, ulna, radial, sciatic and plexus lumbar-sacral, tibia and fibular and its ramifications, in 10 bombardments with final maintenance of 7 seconds. Six sessions were carried out. The participants signed a free and conscious agreement term. The criteria for inclusion were: they could not present any detectable nervous problem through the tests of tension. For exclusion were: missing two or more sessions consecutively and be in any type of physiotherapeutic treatment and/or techniques for flexibility. The data were analyzed statistically through graphics by Microsoft Excel 2003, and tests of normality, Kolmogorov-Smirnov and Shapiro-Wilk, and, for the variables, Wilcoxon and T Test, since p?0,05 determine significance, of the SPSS program for Windows 13.0. The results gotten were meaningful p=0,00 for earning of EMA of knee extension associated to the "Slump Test" and p=0,00 for flexibility. One concluded that Neural Mobilization has brought meaningful improvements onto muscular performance of asymptomatic individuals.
Keywords: Mobilization of Nervous System; Movement Amplitude; Flexibility